2011
DOI: 10.4049/jimmunol.1003907
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for an Evolutionarily Conserved Role of IL-7 Signaling in T Cell Development of Zebrafish

Abstract: In mammals, the cytokine IL-7 is a key regulator of various aspects of lymphocyte differentiation and homeostasis. Because of the difficulty of identifying cytokine homologs in lower vertebrates and the paucity of assay systems and reagents, the degree of functional conservation of cytokine signaling pathways, particularly those pertaining to lymphocyte development, is unclear. In this article, we report on the analysis and characterization of three zebrafish mutants with severely impaired thymopoiesis. The id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…Recent results have underscored the surprising similarities between zebrafish and mammals in many aspects of hematopoietic and immune system development and function (Bertrand and Traver, 2009;Boehm et al, 2003;de Jong and Zon, 2005;Langenau and Zon, 2005;Lesley and Ramakrishnan, 2008;Lieschke and Trede, 2009). For instance, some immunological phenotypes identified in genetic screens in zebrafish are caused by mutations in genes, the mammalian counterparts of which are known to underlie mammalian immunodeficiency syndromes (Iwanami et al, 2011;Wienholds et al, 2002). Collectively, these findings suggest that zebrafish might serve as a general model for studying immune system development.…”
Section: Introductionmentioning
confidence: 95%
“…Recent results have underscored the surprising similarities between zebrafish and mammals in many aspects of hematopoietic and immune system development and function (Bertrand and Traver, 2009;Boehm et al, 2003;de Jong and Zon, 2005;Langenau and Zon, 2005;Lesley and Ramakrishnan, 2008;Lieschke and Trede, 2009). For instance, some immunological phenotypes identified in genetic screens in zebrafish are caused by mutations in genes, the mammalian counterparts of which are known to underlie mammalian immunodeficiency syndromes (Iwanami et al, 2011;Wienholds et al, 2002). Collectively, these findings suggest that zebrafish might serve as a general model for studying immune system development.…”
Section: Introductionmentioning
confidence: 95%
“…This probably formed the basis for the functional diversity, pleiotropy, and redundancy of the CytoRs found in higher vertebrates (83), such as the pleiotropic functions of IL-6R (84) and LIFR (85); the specialist hematopoietic functions of EPOR (65,86), G-CSFR (20,87,88), and TPOR (89); the innate immunity roles of type I and III IFNs (90,91); the stem cell functions of TPOR (92); the neural functions of CNTFR (93); and the roles of GHR, PRLR, and LEPR in growth, metabolism, and reproduction (68,94,95). The increase in components allowed one major additional functionality to emerge, with the IL-2R and IL-3R families and type II IFNs exerting their major effects in adaptive immunity (63,67,74,96). In addition, downstream components originally played pleiotropic roles (97), a property that has been maintained particularly in JAK1, JAK2, STAT3, STAT5, and SOCS3, although other duplicates have developed more specific roles, such as JAK3, STAT4, and STAT6 in adaptive immunity and TYK2, STAT1, STAT2, and SOCS1 in antiviral immunity (5).…”
Section: Consequences and Driversmentioning
confidence: 99%
“…Available evidence suggests that the functions mediated via the majority of these "core" CytoRs have been conserved. For example, analysis in zebrafish showed that GHR functions in controlling growth (60), LEPR functions in metabolic control (61), G-CSFR participates in myelopoiesis (62), IL-7R contributes to T cell development (63) and type II IFNR participates in antiviral responses (64), similar to their mammalian counterparts. This was shown to extend to their downstream pathways where investigated, such as EPOR/JAK2/ STAT5 in erythropoiesis (65,66) and IL-2Rgc/JAK3/STAT5 in T lymphopoiesis (67).…”
Section: Expansion Of the Pathwaymentioning
confidence: 99%
“…Like mammals, zebrafish undergo distinct phases of hematopoiesis, with lymphoid progenitors seeding the thymus early in development following the establishment of definitive hematopoiesis (24). Zebrafish also shows broad conservation of cytokine receptors and downstream signaling pathway components (25,26), particularly those known to facilitate the development of blood and immune cells (27)(28)(29)(30)(31).…”
mentioning
confidence: 99%